Analisis Wacana Rekonstruksi Sejarah 1998 pada Film Pengepungan di Bukit Duri - Prasanti Ayuningtyas Prawirohardjo; Triyono Lukmantoro (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the discourse of historical reconstruction of the 1998 tragedy depicted in the film "Pengepungan di Bukit Duri," amidst the gap in the younger generation's memories of the event. The study employs Van Dijk's Critical Discourse Analysis, encompassing the levels of text, social cognition, and social context. Furthermore, Social Construction Theory and Modes of Reconstrued Realities are also used to support the research. The results show that at the text level, the racist lexicon and visual symbols of the scenes and attributes depicted in the film construct opposition between the majority and the minority, as well as practices of dehumanization. At the social cognition level, the film reflects the ideology of its creator, making it a means of social critique inspired by the 1998 tragedy. At the social context level, the film functions as a medium for the practice of memory politics, shaping commemoration through the social awareness of the younger generation. Theoretically, this research strengthens the relevance of Van Dijk's Critical Discourse Analysis, which examines film as a medium that is not neutral and can be used to convey a certain ideology, and shows how Modes of Reconstructed Realities are processed through the formation of social awareness that is instilled through the social reality displayed in film scenes.